Analisis Strategi Komunikasi Pemasaran Brand Rucas Untuk Membangun Brand Awareness - Aditya Adam Varizky; Delmarrich Bilga Ayu; Rini Ganefwati (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the marketing communication strategy of the RUCAS brand through social media and identify the implementation of advertising, interactive marketing, and direct marketing elements within the strategy. The research method used is qualitative with a descriptive approach. The results indicate that RUCAS's marketing communication strategy focuses on utilizing Instagram and TikTok as the main platforms to build brand identity through creative visual content, before-after concepts, and popular trends. RUCAS also leverages the momentum of events like BYON Combat and LOCALFEST to increase exposure. In the communication mix, advertising is implemented through emotional visual storytelling. Interactive marketing successfully builds two-way engagement through interactive social media features, while direct marketing is conducted through direct product information delivery, teasers, and public figure collaborations. In conclusion, RUCAS's utilization of social media functions not only as a promotional tool but also as a strategic medium to build image, interaction, and sustainable emotional relationships in the digital fashion industry. .